Performance of the Syva Direct Fluorescent Antibody Assay for Chlamydia in a Low-Prevalence Population - Mark B. Reedy; Patricia J. Sulak; William B. McCombs III; Thomas J. Kuehl (Hindawi Limited, 1993)
Chlamydia trachomatis is the most common reportable sexually transmitted disease (STD) in the United States. In the 1980s, rapid diagnostic tests for chlamydia began to replace more cumbersome tissue culture methods. Current data on rapid antigen detection assays demonstrate acceptable sensitivity, specificity, and predictive values in populations with a high prevalence of chlamydia. Few studies report the performance of these assays in a low-prevalence obstetric and gynecologic (Ob/Gyn) population, This study compares the most commonly used direct fluorescent antibody (DFA) assay (Syva Microtrak) with tissue culture (TC) in a low-prevalence population. Endocervical specimens (775) were tested from women at risk for chlamydia infection, and the prevalence was found to be 7.7%. The DFA assay demonstrated a sensitivity of 80% and a specificity of 97% compared with TC. The positive and negative predictive values were 72% and 98%, respectively. The results of this study indicate that the Syva DFA assay lacks the sensitivity and positive predictive value for routine use in Ob/Gyn populations with a lowprevalence of C. trachomatis.